Synthesis of Some Azo Dyes Based on 2,3,3-Trimethyl-3H-indolenine - Bukia, Tinatin; Utiashvili, Mariam; Tsiskarishvili, Manana; Jalalishvili, Sopo; Gogolashvili, Ana; Tatrishvili, Tamara; Petriashvili, Gia (Видавництво Львівської політехніки, 2023)
Нові азосполуки на основі 2,3,3-триметил-3Н-індоленіну синтезовано й охарактеризовано за допомогою ІЧ-, ЯМР- і мас-спектрального аналізу. Синтез проводили трьома різними маршрутами: 1) відновленням нітросполуки за допомогою Zn/NaOH у спирті; 2) нагріванням 2,3,3-триметил-3Н-індоленін-5-аміну в присутності MnO2 в толуолі; 3) діазотуванням 2,3,3-триметил-3Н-індоленін-5-аміну й обробкою отриманої солі діазонію відповідною азоскладовою.

New azo compounds on the base of 2,3,3-trimethyl-3H-indolenine were synthesized and characterized by FT-IR, NMR, and Mas-spectral analysis. The synthesis was conducted in three different pathways: 1) by reducing the nitro compound with Zn/NaOH in alcohol; 2) by heating of 2,3,3-trimethyl-3H-indolenine-5-amine in the presence of MnO2 in toluene, and 3) by diazotization of 2,3,3-trimethyl-3H-indolenine-5-amine and treating the resulting diazonium salt with the appropriate coupler.
Синтез деяких азобарвників на основі 2,3,3 триметил 3H індоленіну
Keywords: азобарвники; біс-азобарвник; відновлення; 2; 3; 3-триметил-3Н-індоленін; синтез; azo dyes; bis azo dye; reduction; 2; 3; 3-trimethyl-3H-indolenine; synthesis